Os princípios constitucionais ambientais dos estados partes do Mercado Comum do Sul - Costa, Ervandil Corrêa (2009)
This study aimed at analyzing the environmental principles present in the Constitution of Mercosur Member States. Therefore, as a presupposed, we initially carried out an approach of points that are considered significant in the context of the economic integration in relation to the anthropocentric activity versus environment and, from this point constructing, from this view, a connection of the Mercosur formation history, as an informative feature in relation to the environment protection. In this context, we based the study through a reflection about the Environmental Law in vigor at the countries that are members of the Mercosur and in Latin America. Next, we established a discussion about the historicity of Mercosur constitution, highlighting as pyramidal points, the most significant events in the block construction since the Asunción Treat. We emphasized, along the text, the environment as an important element in the political and socioeconomic integration. In the final part of the work, we made an interpretative and prospective analysis of the environmental principles: fundamental human right; property social function; equity; sustainable development; precaution; prevention; polluter-pays; information; participation and cooperation that are present in the Constitutions of Argentina, Brazil, Paraguay and Uruguay. In the discussion, we highlighted the similarity of environmental principles inserted in the constitutional devices as well as the harmonization of these environmental rules. The results made it possible to adduce that during the period of the Southern Common Market construction, there was a progressive valorization of the environment, due to the elaboration of harmonized environmental rules, consequence of meetings which resulted in the production of important documents about environmental tutelage. Later on, there was a stagnation of this process. It is also unquestionable, that the paradigm adopted in the formation of the Southern Common Market was based in the principles inserted in the International Environmental Law and in the EU Constitutive Acts. Finally, to make this work proposal operative, we used the comparative process which allowed us to affirm that the principles of fundamental human right, property social function, equity, polluterpays and participation were found as present in the Constitution of Argentina, Brazil, Paraguay and Uruguay. Although, we understand that all the principles listed to the analysis of this study are present only in the Constitution of Argentina and Brazil. Therefore, we can say that there are neither similarities of environmental principles in the Constitution of all Mercosur States nor a harmonization of environmental legislation with Constitutional support.